The Effect of Size Project Based Learning on Problem Solving Skills In Government Science Students - Pasaribu, Daniel (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study was to determine the effect of Size Problem Based Learning on problem solving ability in government science students. This study is a type of meta-analysis research. Data sources in this study come from 10 national and international journals published from 2020-2024. The criteria for data eligibility are research derived from SINTA and Scopus indexed journals and proceedings, participants in this study of social science students, research related to the effect of size project based learning on problem solving ability in political science students, and the sample size must be large 20 students. Purposive sampling data collection techniques. Data analysis is calculating the effect size value with the help of Microsoft Excel 2020. The results of the study concluded that there was a significant influence of differentiation learning on the profile of Pancasila students in social science students in Indonesia with an average value of effect size 10 studies of 0.878 and Standard error of 0.342 with a high effect size category.